A rare case of rhino-orbito-maxillary mucormycosis having no common signs and laboratory findings but no visible morbidity - Khare, Aarti Mahesh; Nemane, Sachin Tukaram; Javade, Prashant Shridhar; Narkhede, Yogesh Pralhad; Parti, Punita A. (Indian Journal of Case Reports, 2021)
Mucormycosis is an opportunistic fungal infection caused by omnipresent fungi called Mucorales of class Phycomycetes. It mainly occurs in immunocompromised patients, and only early diagnosis with medical and surgical intervention remains the gold standard in managing it. Here, we present the case of a patient contracted with mucormycosis post his COVID-19 infection involving the rhino-orbito-maxillary area. The patient presented to our hospital with dental pain a month after his discharge. Since the mucormycosis cases were at a peak in this period, our team of doctors did a thorough examination of the patient, which revealed dental and ophthalmologic abnormalities. No clinical necrotic eschar in the palatine or nasal cavity was diagnosed, but magnetic resonance imaging (MRI) revealed a typical COVID-19 mucormycosis infection. Accordingly, prompt treatment with systemic amphotericin B was started. However, as the patient declined surgical intervention, we feared the worst outcome, which to our surprise showed no adverse progression.